2017
DOI: 10.1002/pbc.26568
|View full text |Cite
|
Sign up to set email alerts
|

Malignant ovarian germ cell tumors in pediatric patients: The AIEOP (Associazione Italiana Ematologia Oncologia Pediatrica) study

Abstract: Objective: Malignant ovarian germ cell tumors (MOGCT) carry an excellent prognosis, and the treatment aims to achieve results with the least possible treatment-related morbidity. The aim of this study was to assess the outcomes of pediatric patients with MOGCT. 5-year overall survival [OS] 100%), seven relapsed (three patients with Dysg and four patients with Non-Dysg) and were rescued with chemotherapy (plus surgery in three patients). Among the evaluable patients with stages II-IV, 48 (98%) achieved complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…28 Although the majority of patients are cured by surgery and chemotherapy, a subgroup of them relapse. [29][30][31][32][33] Current therapeutic options are effective in less than 50% of patients with high-risk disease, indicating that more effective and less toxic therapies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…28 Although the majority of patients are cured by surgery and chemotherapy, a subgroup of them relapse. [29][30][31][32][33] Current therapeutic options are effective in less than 50% of patients with high-risk disease, indicating that more effective and less toxic therapies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Males with pure T, or nonÀgerm-cell component were excluded. Patients were followed up with abdominal ultrasound and chest X-rays, clinical examinations, aFP, and b-hCG assay as described elsewhere [4]. Staging was done according to the Children's Oncology Group (COG) [5], modified system (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Response criteria were as reported elsewhere [4]. If marker levels were high at diagnosis, cases were only classified as progressing if tumor growth coincided with further increasing marker levels.…”
Section: Treatment and Response Criteriamentioning
confidence: 99%
“…The current standard management protocol for MOGCT is complete cytoreductive surgery followed by adjuvant chemotherapy, as in this case. However, just surgical treatment without adjuvant chemotherapy has recently been proposed for patients with FIGO stage 1 ovarian tumors [7,8]. In a study of 25 children and adolescents with a mean age of 12 years, Billmire, et al [9] evaluated the surgery-only, watch-and-wait strategy and found that the overall oncologic outcomes were not impaired and 50% of the patients avoided having to take adjuvant chemotherapy.…”
Section: Conflicts Of Interestmentioning
confidence: 99%